Transcript Profiling Identifies NAC-Domain Genes Involved in Regulating Wall Ingrowth Deposition in Phloem Parenchyma Transfer Cells of Arabidopsis thaliana - Wu, Yuzhou; Hou, Jiexi; Yu, Fen; Nguyen, Suong T. T.; McCurdy, David W. (Frontiers in Plant Science, 2018)
Transfer cells (TCs) play important roles in facilitating enhanced rates of nutrient transport at key apoplasmic/symplasmic junctions along the nutrient acquisition and transport pathways in plants. TCs achieve this capacity by developing elaborate wall ingrowth networks which serve to increase plasma membrane surface area thus increasing the cell’s surface area-to-volume ratio to achieve increased flux of nutrients across the plasma membrane. Phloem parenchyma (PP) cells of Arabidopsis leaf veins trans-differentiate to become PP TCs which likely function in a two-step phloem loading mechanism by facilitating unloading of photoassimilates into the apoplasm for subsequent energy-dependent uptake into the sieve element/companion cell (SE/CC) complex. We are using PP TCs in Arabidopsis as a genetic model to identify transcription factors involved in coordinating deposition of the wall ingrowth network. Confocal imaging of pseudo-Schiff propidium iodide-stained tissue revealed different profiles of temporal development of wall ingrowth deposition across maturing cotyledons and juvenile leaves, and a basipetal gradient of deposition across mature adult leaves. RNA-Seq analysis was undertaken to identify differentially expressed genes common to these three different profiles of wall ingrowth deposition. This analysis identified 68 transcription factors up-regulated two-fold or more in at least two of the three experimental comparisons, with six of these transcription factors belonging to Clade III of the NAC-domain family. Phenotypic analysis of these NAC genes using insertional mutants revealed significant reductions in levels of wall ingrowth deposition, particularly in a double mutant of NAC056 and NAC018, as well as compromised sucrose-dependent root growth, indicating impaired capacity for phloem loading. Collectively, these results support the proposition that Clade III members of the NAC-domain family in Arabidopsis play important roles in regulating wall ingrowth deposition in PP TCs.